GM-002 Improving medicines management in the hospital discharge setting through pharmacist intervention in the synchronisation of computer applications. (24th March 2015) - Villamañán, E; Lara, C; Ruano, M; Baumann, T; Balade, L; Varela, H; Herrero, A
Abstract : Background: Lack of synchronisation between hospital applications involved in the medicines use process (MUP) leads to inefficient use of resources. Purpose: To prove that pharmacist intervention (PI) in the integration of information recorded in computer applications improves medicines management in the discharge setting (DS). Material and methods: Longitudinal, prospective, study (10 days) in a tertiary hospital (1, 350 beds). Adult patients being discharged from medical and surgical specialties were evaluated (410 beds). Discharges are recorded in a bed management computer application (BMCA). Every 20 min this information is transferred to CPOE so that electronic prescriptions (EPs) are automatically inactivated. At discharge, because of lack of synchronisation, EPs were incorrectly remaining active. This outdated information was transferred to the automated pharmacy medicines dispensing systems (APMDS) which meant that these medicines were being dispensed to the ward as if the discharged patients were being admitted. Subsequently, they were returned to the pharmacy. Pharmacists confirmed discharges daily, consulting the BMCA. Once verified, they updated EPs in CPOE, avoiding unnecessary dispensing of medicines. Primary endpoint: number of EPs updated by PI in COPE. We also analysed the number of medicines whose unnecessary dispensing and subsequent return to pharmacy was avoided by PI and working time saved. Results: We evaluated 361 patients DS. PI updated EPs of 132 (36.6%) outdated because of lack of synchronisation between BMCA and CPOE. The remaining 229 didn't require PI, as the information recorded in CPOE when it was transferred to APMDS was correct. 1, 012 EPs out of 3, 327 (30.4%) were updated by PI. Without PI, these prescriptions would have generated unnecessary dispensing of 3, 601 medicines. PI led to a total saving of 9.36 h of two pharmacy technicians' work re-entering medicines unnecessarily dispensed to the ward. Conclusion: PIs reduced dispensing failures arising from lack of real-time transmission between hospital applications. Greater synchronisation between BMCA and CPOE would have avoided most of them. PIs improved MUP in DS, saving time and avoidable pharmacy workload. Reference: Nursing staff No conflict of interest.